Syntheses and biological evaluation of new triazole-spirochromone conjugates as inhibitors of mycobacterium tuberculosis - Muthukrishnan, Murugan; Mujahid, Mohammad; Yogeeswari, P.; Sriram, D. (Tetrahedron Letters, 2011)
A series of novel 1,2,3-triazole fused spirochromone conjugates have been synthesized bearing both spirochromone moiety as well as a 1,2,3-triazole moiety. Some of the compounds have exhibited potential activity against Mycobacterium tuberculosis (virulent strain H37Rv). In particular 5e proved to be the most potent derivative exhibiting MIC = 0.78 mu g/mL. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Antitubercular activity; Click chemistry; Mycobacterium tuberculosis; Spirochromones